Altered tumor microenvironment heterogeneity of penile cancer during progression from non‐lymphatic to lymphatic metastasis - Da‐Ming Xu; Xiao‐Yu Zhuang; Hua‐Li Ma; Zai‐Shang Li; Li‐Chao Wei; Jun‐Hang Luo; Hui Han (Cancer Medicine)
Abstract Background Lymphatic metastasis is the major challenge in the treatment of penile cancer. The prognosis of individuals with lymphatic metastasis is extremely poor. Therefore, early identification of disease progression and lymphatic metastasis is an urgent task for researchers in penile cancer worldwide. Methods In this study, using single‐cell RNA sequencing, an immune landscape was established for the cancer ecosystem based on 46,861 cells from six patients with penile cancer (four with lymphatic metastasis [stage IV] and two without lymphatic metastasis [stage I]). Using bulk RNA sequencing, the discrepancy between the cancers and their respective metastatic lymph nodes was depicted based on seven patients with penile cancer. Results The interaction between epithelial cells, fibroblasts, and endothelial cells, and the functional cooperation among invasion, epithelial‐mesenchymal transition, and angiogenesis were found to be important landscapes in the penile cancer ecosystem, playing important roles in progression of cancer and lymph node metastasis. Conclusions This study is the first to investigate the altered tumor microenvironment heterogeneity of penile cancer as it evolves from non‐lymphatic to lymphatic metastasis and provides insights into the mechanisms underlying malignant progression, the premetastatic niche, and lymphatic metastasis in penile cancer.